Confronting Antisemitism from the Perspectives of Christianity, Islam, and Judaism - Lange, Armin; Lange, Armin; Mayerhofer, Kerstin; Porat, Dina; Schiffman, Lawrence H. (Berlin/Boston De Gruyter, 2020)
This volume engages with antisemitic stereotypes as religious symbols that express and transmit a belief system of Jew-hatred. These religious symbols are stored in Christian, Muslim and even today's secular cultural and religious memories. This volume explores how antisemitic religious symbol systems can play a key role in the construction of group identities.
Keywords: Traditions of antisemitism